BLENDED LEARNING IN DENTAL EDUCATION - Supriya Bhat; Medhini Madi (Cumhuriyet University, 2022)
The Dental education sector has witnessed a lot of innovations in the past decade. Technology has played an important role in achieving this revolution such that the student can pursue the learning process at any given time and place beyond the geographical limits. The most frequently used approach is the concept of blended learning, which is an amalgamation of face-to-face and online modes of education. Thus its role in ensuring the learning process to students all over the world despite the COVID 19 pandemic is innumerable. Hence, this review was conducted to explore how different dentistry fields have adopted this approach as a useful tool to impart dental education. The PUBMED database was used to retrieve the articles about the same using the search terms "Blended Learning" AND "dental education". The majority of the studies showed a positive response and a higher level of satisfaction in comparison to conventional teaching. However, certain studies also indicated no significant improvement in knowledge compared to conventional methods. Conventional methods will definitely continue to be the mainstay as certain themes cannot be dealt with otherwise. In such cases, blending online as well as traditional methods would give beneficial results while preserving the feel of the live personal interaction.